Do ESG Controversies Matter for Firm Value? Evidence from International Data - Aouadi, Amal; Marsat, Sylvain (Journal of business ethics, 2018)
The aim of this paper is to investigate the relationship between environmental, social, and governance (ESG) controversies and firm market value. We use a unique dataset of more than 4000 firms from 58 countries during 2002-2011. Primary analysis surprisingly shows that ESG controversies are associated with greater firm value. However, when interacted with the corporate social performance (CSP) score, ESG controversies are found to have no direct effect on firm value while the interaction appears to be highly and significantly positive. Building on this evidence, we attempt to explore the channels through which CSP may enhance market value. Conducting sample split analysis indicates that higher CSP score has an impact on market value only for high-attention firms, those firms which are larger, perform better, located in countries with greater press freedom, more searched on the Internet, more followed by analysts, and have an improved corporate social reputation. Thus, our findings provide new insights on the role of firm visibility through which firms can profit from their CSP.